Pengaruh Disiplin Kerja, Komunikasi Kerja, dan Kompensasi terhadap Kinerja Karyawan pada Cv Sinar Wijaya Motor - Malinda Setyaning Lilla; Brahma Wahyu; Umi Nadhiroh (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to determine the influence of work discipline, work communication and compensation on employee performance. This type of research is quantitative research. This research data was obtained through primary and secondary data. The population in this study were employees at CV Sinar Wijaya. The sample in this study was 60 employees with a sampling technique using the Slovin formula. The analysis techniques used are validity testing, reliability testing, classical assumption testing, multiple linear regression analysis and hypothesis testing. The research results show that the partial t test results of the variables discipline, work communication and compensation have an effect on employee performance. The results of the F test simultaneously show that discipline, work communication and compensation influence employee performance.